Performance Analysis of Age Invariant Face Recognition Methods - Jebina, H; Beham, M. Parisa; Roomi, S. Md. Mansoor (International Journal of Computer Sciences and Engineering, 2025)
Age Invariant Face Recognition is an emerging research topic in Face Recognition Research Community has many practical applications such as in law enforcement, identifying criminals, passport renewal etc. Facial Aging has not received adequate attention compared to other sources of variations due to pose, lighting, and expression. This paper aims to give a detailed survey of age invariant face recognition. This review covers the techniques that attempt to solve the age invariant problems. This paper also discusses different techniques to extract features and textures of age invariant facial part. Existing problems in age invariant face recognition are covered and possible solutions are suggested in this review. Advantage and disadvantage of each methods and recognition accuracy have been discussed